Peroxisome Biogenesis: Involvement of ARF and Coatomer - Passreiter, Michael (The Rockefeller University Press, 1998)
Peroxisomal membrane protein (Pmp)26p (RnPex11p), a major constituent of induced rat liver peroxisomal membrane, was found to contain a COOH-terminal, cytoplasmically exposed consensus dilysine motif with the potential to bind coatomer. Biochemical as well as immunocytochemical evidence is presented showing that peroxisomes incubated with preparations of bovine brain or rat liver cytosol recruit ADP-ribosylation factor (ARF) and coatomer in a strictly guanosine 5′-O-(3-thiotriphosphate)–dependent manner. Consistent with this observation, ldlF cells expressing a temperature-sensitive mutant version of the ε-subunit of coatomer exhibit elongated tubular peroxisomes possibly due to impaired vesiculation at the nonpermissive temperature. Since overexpression of Pex11p in Chinese hamster ovary wild-type cells causes proliferation of peroxisomes, these data suggest that Pex11p plays an important role in peroxisome biogenesis by supporting ARF- and coatomer-dependent vesiculation of the organelles.